2007
DOI: 10.1007/s00381-007-0427-1
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in ethanol-treated mice with folic acid supplementation in saccharose

Abstract: The study demonstrated that dietary supplementation with folate in saccharose is an accessible means of consumption that could be further diffused but in an increased dose than recommended to reduce the teratogenic effects of ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…This may result in too few cells for fusion of the neural folds (Copp et al, 2003; Greene and Kopp, 2006). Animal models also suggest that alcohol exposure may play an indirect role in NTD development (Yanaguita et al, 2008) by contributing to folic acid deficiency via increased excretion of folic acid by the kidneys (McMartin, 1984; Muldoon and McMartin, 1994). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may result in too few cells for fusion of the neural folds (Copp et al, 2003; Greene and Kopp, 2006). Animal models also suggest that alcohol exposure may play an indirect role in NTD development (Yanaguita et al, 2008) by contributing to folic acid deficiency via increased excretion of folic acid by the kidneys (McMartin, 1984; Muldoon and McMartin, 1994). …”
Section: Discussionmentioning
confidence: 99%
“…Alcohol is a known teratogen, with effects that may be more pronounced during organogenesis (Yanaguita et al, 2008). A potential association between alcohol consumption and NTDs was first described in a case series more than 25 years ago (Friedman, 1982); however, the biological mechanisms by which alcohol impacts neural tube development are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, with a folate free diet, a low ethanol dose was as deleterious as a high dose. Yanaguita et al (2008) concluded that supplementation with the recommended dose of folic acid (2 mg/kg), was not effective in preventing the deleterious teratogenic effects induced by ethanol, indicating the need for an increased dose. Firat et al (2005) in their experiment on rats, administered Retinoic acid in different doses, orally on GD8.…”
Section: Discussionmentioning
confidence: 99%
“…Folic acid has been shown to reduce the incidence of neural tube defects caused by valproic acid (Dawson et al, 2006;Padmanabhan and Shafiullah, 2003) retinoic acid (Reynolds et al, 2003;Firat et al, 2005), ochratoxin A (Katagiri et al 2007), Fumonisin B1 (Sadler et al, 2002), ethanol (Yanaguita et al, 2008), arsenic (Gefrides et al, 2002) and hyperthermia (Shin and Shiota, 1999;Li et al, 2003). Its role in the prevention of other congenital defects has not yet been fully explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation